Pengaruh Efikasi Diri terhadap Prestasi Akademik dan Keterlibatan Belajar: Sebuah Tinjauan Literatur Sistematis - Rizka Indah Primawati; Wiji Wiji; Sri Mulyani (Jurnal Penelitian Pendidikan IPA, 2026)
Academic self-efficacy is a critical psychological construct consistently linked to student success. However, the extensive body of research is fragmented, necessitating a systematic synthesis to understand the key factors, outcomes, and underlying mechanisms associated with student’s self-efficacy. The purpose of this systematic literature review is to synthesize and evaluate the current evidence on the effect of self-efficacy on academic achievement and learning engagement. Following the PRISMA guidelines, a comprehensive search was conducted across Science Direct database. The review synthesized findings from 25 articles, focusing on empirical studies that examined the antecedents and consequences of self-efficacy in relation to academic outcomes. The findings reveal that self-efficacy serves as a significant predictor of academic achievement and learning engagement. Results indicate that students with high self-efficacy demonstrate greater persistence, set more ambitious goals, and exhibit higher resilience in challenging subjects. The discussion highlights that this relationship is mediated by both social support and cognitive engagement strategies. In conclusion, developing self-efficacy is essential for optimizing educational outcomes